Effect of Decamon Application and Eggshells Waste on the Growth and Productivity of Mini Chung Cherry Tomato (Solanum lycopersicum var. cerasiforme.) - Wulandari, Putri; Ratnasari, Evie (LenteraBio : Berkala Ilmiah Biologi, 2023)
Indonesia is one of the countries whose market demand for vegetables especially tomatoes, is increasing every year. Therefore, it is necessary to make efforts to accelerate the growth and productivity of tomato plants. The effort that can be done is the addition of growth regulators, one of which is dekamon. The purpose of this study was to determine the effect of giving dekamon and eggshell waste on the growth and productivity of cherry tomato (Solanum lycopersicum) var. cerasiforme. The study used a randomized block design (RBD) with several doses including 1 ml; 2ml; 3ml; 4 ml and control with five repetitions. Parameters observed included plant height, leaves quantity, diameter of stem, and fruit quantity. Data analysis was performed using ANOVA and continued with Duncan’s test. The results showed that there was an effect of giving dekamon and eggshell waste on plant growth and productivity. Application of egg shell waste and 4 ml of dekamon was the best treatment for all parameters including plant height 82.28 ± 1.29, leaves quantity 28.80 ± 1.64, diameter of stem 5.88 ± 0.16, and fruit quantity 5.88 ± 0.16